2004
DOI: 10.1023/b:nere.0000018859.23881.f9
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Myo-inositol and Plasmalogen Metabolism in Rat Brain

Abstract: Plasmalogens are ether-linked phospholipids that are abundant in nervous tissues. Their biological role is unclear, but may involve membrane structure/function and antioxidant activities. This study further investigates a recent report that chronic administration of myo-inositol in rats increased brain phosphatidylethanolamine plasmalogen (PlsEtn). We examined the effects of myo-inositol administration on the incorporation of [2-(13)C]ethanolamine ([2-(13)C]Etn) into rat brain phospholipids using NMR spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(59 citation statements)
references
References 35 publications
9
49
1
Order By: Relevance
“…The addition of Etn containing 13 C isotope enrichment enabled us to monitor the biosynthesis of Etn lipids in the brain by NMR. Our results demonstrated that the acute myo-Ins + Etn administration yielded a 30% increase in whole brain PlsEtn concentrations, a 16% increase in its mole percentage of phospholipids and a 47% increase in the biosynthesis of newly synthesized Etn lipids (12). We also demonstrated a strong positive correlation between the brain myoIns concentration and PlsEtn concentration.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The addition of Etn containing 13 C isotope enrichment enabled us to monitor the biosynthesis of Etn lipids in the brain by NMR. Our results demonstrated that the acute myo-Ins + Etn administration yielded a 30% increase in whole brain PlsEtn concentrations, a 16% increase in its mole percentage of phospholipids and a 47% increase in the biosynthesis of newly synthesized Etn lipids (12). We also demonstrated a strong positive correlation between the brain myoIns concentration and PlsEtn concentration.…”
Section: Introductionsupporting
confidence: 62%
“…Recently, our laboratory further investigated this phenomenon using several protocols involving chronic and acute administration of myo-Ins ± ethanolamine (Etn) in rats (12). The addition of Etn containing 13 C isotope enrichment enabled us to monitor the biosynthesis of Etn lipids in the brain by NMR.…”
Section: Introductionmentioning
confidence: 99%
“…The increased ratio of plasmalogens to phospholipids (Plas/PL) after myo-inositol treatment was greater than that of the actual plasmalogen level (Table 2), which means a specific enhancement of plasmalogen biosynthesis in glycerophospholipids. Myo-inositol is reported to increase the brain plasmalogen content in rats (10), and this effect may contribute to improve affective disorders, such as major depression and panic disorder (11). Although the mechanism by which myo-inositol enhances plasmalogen biosynthesis remains unknown, myo-inositol intake possibly facilitates plasmalogen biosynthesis in the liver, and this may lead to the secretion of plasmalogen-rich lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Pls are major component of myelin membranes, and essential for myelin formation and functions. In animal studies, oral administration of MI showed to increase Pls level in rat brain (Hoffman-Kuczynski & Reo, 2004). Therefore, we have undertaken MI intervention study to investigate whether MI administration improves the dyslipidemia of MetS through facilitating Pls biosynthesis, and to explore the relationship between serum Pls and sdLDL.…”
Section: Intervention Study Of Increasing Serum Plsmentioning
confidence: 99%